Immune system modulation in aging: Molecular mechanisms and therapeutic targets - Cisneros, Bulmaro; García-Aguirre, Ian; Unzueta, Juan; Arrieta-Cruz, Isabel; González-Morales, Oscar; Domínguez-Larrieta, Juan M.; Tamez-González, Aura; Leyva-Gómez, Gerardo; Magaña, Jonathan J. (Frontiers in Immunology, 2022)
The function of the immune system declines during aging, compromising its response against pathogens, a phenomenon termed as immunosenescence. Alterations of the immune system undergoing by aged individuals include thymic involution, defective memory T cells, impaired activation of naïve T cells and weak memory response. Age-linked alterations of the innate immunity comprise perturbed chemotactic, phagocytic and natural killing functions, as well as impaired antigen presentation. Overall, these alterations result in chronic low-grade inflammation (inflammaging) that negatively impacts on health of elderly people. In this review we address the most relevant molecules and mechanisms that regulate the relationship between immunosenescence and inflammaging, and provide an update description of the therapeutic strategies aimed to improve immunity in aged individuals.